When time become linear - Carvalho, Silvia M. S. (Universidade Estadual Paulista / UNESP, 2009)
Based in an essay of Edmund Leach about time, we've tried to specify certain enlightened by the Knowledge we have today about the hunters and gatherers and their space-representations. We've also tried to establish the relevance that they have to the emergence time representation, technological development and the appear ance of salvation religions; and out that, even in these last, a certain cyclical representation structure is maintained.